Diazotrophic bacteria in the initial growth and biochemical changes of Vigna unguiculata under water deficit (Research, Society and Development, 2020)
The cultivation of cowpea beans has stood out for being an adaptable crop for the arid and semi-arid region of Northeast Brazil. Among the factors that reduce its production, the water deficit and fertilization, stands out. Due to its ability to perform symbiosis with nodulating bacteria, it can optimize the fixation of atmospheric N2 depending on the combination and compatibility of the strains involved. The objective of the work was to evaluate the response of cowpea plants (cultivar BRS Marataoã) under water deficit inoculated and co-inoculated with nitrogen fixing bacteria. The experimental design used was completely randomized in a split plot scheme with two factors (4x5), consisting of: T1: BR3264 (A); T2: BR85 (B); T3: BR3264 + BR85 (C); T4: nitrogen control (CN); T5: absolute control (CA), associated with the water depths in the following proportions: 100%, 80%, 60% and 40% of the crop evapotranspiration (ETc). The analyzes were performed at 45 days after emergence (DAE) and composed of phylotechnical parameters (number of leaves, plant height, stem diameter, chlorophyll a, total b) and biochemical (total soluble sugar, reducing sugar, and proline). The results obtained demonstrated that the water deficit caused a negative influence on the number of leaves, on the stem diameter, on the height of the plants, on chlorophyll A, on the dry mass of the aerial part and on the inoculation. The inoculation of rhizobia strains is reduced when subjected to plants with water stress, with emphasis on native strains. Since cross-inoculation favors inoculation in these conditions.